Research on environmental threats associated with waste management in Ukraine and the world and their impact on ecosystems - Chupryna, Iu. (Ways to Improve Construction Efficiency, 2024)
The article examines environmental threats arising from improper waste management, both at the global and local levels. Particular attention is paid to the analysis of the impact of waste on the environment, in particular on aquatic, soil and atmospheric ecosystems. It has been established that the main sources of pollution are organic and inorganic waste accumulated in landfills and in water bodies, as well as toxic compounds formed during waste incineration. The assessment of environmental threats includes an analysis of the consequences for flora and fauna, as well as for human health. At the same time, the authors provide examples of effective waste management practices implemented in individual countries and consider the possibilities of their adaptation in Ukraine. One such example is the use of innovative technologies for waste processing, such as biogas plants, which allow reducing the amount of waste going to landfills and at the same time generating energy. Other examples include technologies for recycling plastics, which allow reducing environmental pollution and economically reusing materials. An important aspect is also the need to integrate waste management into sustainable development systems, which include not only environmental, but also social and economic aspects. This requires political will at the state level, as well as the development of legislative initiatives for environmental education and raising environmental awareness of the population. The study shows that proper waste management not only reduces environmental pollution, but also creates new opportunities for economic development, in particular through the creation of jobs in the waste processing and disposal industry. In particular, the growth of the waste processing industry leads to the creation of new jobs, the development of small and medium-sized enterprises, and the attraction of investments in the sustainable development sector. In Ukraine, the problem of waste management remains relevant, especially in the context of the low efficiency of existing landfills and the lack of a sufficiently developed infrastructure for recycling. However, with the growth of the volume of accumulated waste, it becomes clear that traditional methods, such as storing waste in landfills, cannot be a long-term solution. An important step towards change is the introduction of separate waste collection, which allows for the effective sorting of materials that can be reused.for waste processing, such as biogas plants, which allow reducing the amount of waste going to landfills and at the same time generating energy. Other examples include technologies for recycling plastics, which allow reducing environmental pollution and economically reusing materials. An important aspect is also the need to integrate waste management into sustainable development systems, which include not only environmental, but also social and economic aspects. This requires political will at the state level, as well as the development of legislative initiatives for environmental education and raising environmental awareness of the population. The study shows that proper waste management not only reduces environmental pollution, but also creates new opportunities for economic development, in particular through the creation of jobs in the waste processing and disposal industry. In particular, the growth of the waste processing industry leads to the creation of new jobs, the development of small and medium-sized enterprises, and the attraction of investments in the sustainable development sector. In Ukraine, the problem of waste management remains relevant, especially in the context of the low efficiency of existing landfills and the lack of a sufficiently developed infrastructure for recycling. However, with the growth of the volume of accumulated waste, it becomes clear that traditional methods, such as storing waste in landfills, cannot be a long-term solution. An important step towards change is the introduction of separate waste collection, which allows for the effective sorting of materials that can be reused.